Wellbeing, burnout and substance use amongst medical students: A summary of results from nine countries. (September 2022) - Kadhum, Murtaza; Ayinde, Olatunde O; Wilkes, Chris; Chumakov, Egor; Dahanayake, Dulangi; Ashrafi, Agaah; Kafle, Bikram; Lili, Rossalina; Farrell, Sarah; Bhugra, Dinesh; Molodysnki, Andrew
Objective: There has been increasing interest in the physical health, mental wellbeing and burnout afflicting medical students over recent years. This paper describes the overall results from phase two of an international study including a further nine countries across the world. Methods: We sampled large groups of medical students in nine countries at the same time and with exactly the same method in order to aid direct comparison of demographics, burnout and mental wellbeing through validated instruments. Results: A total of 4, 942 medical students from these countries participated in this study. Around 68% of respondents screened positive for mild psychiatric illness using the General Health Questionnaire-12. Around 81% and 78% of respondents were found to be disengaged or exhausted respectively using the Oldenburg Burnout Inventory. Around 10% were found to be CAGE positive and 14% reported cannabis use. The main source of stress reported by medical students was their academic studies, followed by relationships, financial difficulties and housing issues. Conclusion: Cultural, religious and socioeconomic factors within each country are important and understanding their effects is fundamental in developing successful local, regional and national initiatives. Further quantitative and qualitative research is required to confirm our results, clarify their causes and to develop appropriate preventative strategies.